2022
DOI: 10.1155/2022/7471246
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Secreted from Adipose-Derived Stem Cells Are a Potential Treatment Agent for Immune-Mediated Alopecia

Abstract: Background. Alopecia has become an exceedingly prevalent dermatological disorder. Etiologically, infection (bacterial and fungal infection), inflammation, and immune dysregulation are the main causes of immune-mediated hair loss. Treating hair loss has remained challenging as the available therapies are limited. Exosomes from adipose-derived stem cells (ADSC-Exos) have been used for treating neurodegenerative diseases and autoimmune diseases and in wound-healing treatments. However, the function and mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…ADSC-Exos treated in vivo skin showed increased expression of Wnt3A, AXIN2, and SFRP1 mRNA. This study provides the potential for developing ADSC-Exos as promising therapeutic EVs for immune-mediated alopecia ( Li et al, 2022 ).…”
Section: Cell-derived Nanovesicles and Their Action Of Mechanism For ...mentioning
confidence: 99%
See 2 more Smart Citations
“…ADSC-Exos treated in vivo skin showed increased expression of Wnt3A, AXIN2, and SFRP1 mRNA. This study provides the potential for developing ADSC-Exos as promising therapeutic EVs for immune-mediated alopecia ( Li et al, 2022 ).…”
Section: Cell-derived Nanovesicles and Their Action Of Mechanism For ...mentioning
confidence: 99%
“…Another study showed that human neural progenitor cell - derived EVs containing miR-100-5p increased the levels of β-catenin, C-myc, and Cyclin D1 in DPCs and these effects were abolished when miR-the DPCs were treated with miR-100-5p inhibitors ( Cao et al, 2021 ). Finally, mouse ADSC-derived EVs were shown to carry low levels of miR-22-5p and miR-22-3p; use of inhibitors against miR-22 diminished the hair inductive ability ( Li et al, 2022 ). These results suggest that miR-100-5p, miR-22-5p, and miR-22-3p have a critical role in activating β-catenin-relayed signaling pathways.…”
Section: The Mechanisms Of Action Of Extracellular Vesicles Cargoes I...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, EVs have emerged as potential therapeutic candidates for various diseases, including ischemic diseases, wound healing, and hair regrowth, by delivering their cargo to target cells[ 8 - 12 ]. EVs or nanovesicles from DP cells[ 13 - 17 ], fibroblasts[ 18 , 19 ], stem cells[ 11 , 20 ], macrophages[ 21 , 22 ] and neural progenitor cells[ 23 ] have been shown to have potential therapeutic effects on hair growth in recent studies. Nearly half of these studies have reported enhanced hair regrowth using DP cells as the source cells, which showed potential as therapeutic candidates for hair regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Wnt/-catenin signaling pathway was activated in the skin of ADSC-Exosome-treated mice, according to qRT-PCR and western blotting data. ADSC-Exosome therapy improved hair regeneration via modifying miR-22, the Wnt/-catenin signaling system, and the TNF-signaling pathway, indicating that ADSC-Exosome may be a potential cell-free therapeutic strategy for immune-mediated alopecia [ 51 ].…”
Section: Mechanism Of Action Of Secretome On Treating Alopeciamentioning
confidence: 99%